An Interactive Comparison of WhatsApp, Telegram, and Google Classroom: Usability and User Experience Insights - Alsanossi, Reem; Mohammed, Mona (AlQalam Journal of Medical and Applied Sciences, 2025)
This study presents a comprehensive comparative analysis of the usability and user experience of three widely utilized applications: WhatsApp, Telegram, and Google Classroom. Grounded in the ISO 9241-11 framework and Human-Computer Interaction (HCI) principles, the research examines these applications across key dimensions, including efficiency, effectiveness, and user satisfaction. A quantitative descriptive methodology was adopted, involving a Likert-scale survey distributed among 71 participants, including faculty members, postgraduate students, and undergraduate students specializing in IT disciplines. The data collected were analyzed using SPSS through descriptive statistics, T-tests, ANOVA, and correlation analyses. The results reveal that WhatsApp leads in user satisfaction and daily usability due to its simplicity and adaptability to routine communication needs. Telegram is preferred for its superior privacy features and support for advanced functionalities, making it ideal for secure communication and academic purposes. Google Classroom, while excelling in educational effectiveness, faces usability challenges in real-time communication and adaptability. Additionally, user feedback highlights key areas for improvement, such as enhancing privacy in WhatsApp, improving file upload reliability in Telegram, and refining Google Classroom’s interface for broader accessibility. This study provides valuable insights for application developers, educators, and researchers, emphasizing the need for tailoring applications to diverse user contexts and enhancing their usability to meet evolving demands.